Representation of Algebraic Integers as Sum of Units over the Real Quadratic Fields (Baghdad Science Journal, 2019)
In this paper we generalize Jacobsons results by proving that any integer in is a square-free integer), belong to . All units of are generated by the fundamental unit having the formsour generalization build on using the conditionsThis leads us to classify the real quadratic fields into the sets Jacobsons results shows that and Sliwa confirm that and are the only real quadratic fields in .